Homoeopathy for One Health-One Nation (Homoeopathy for All, 2024)
Now-a-days, the public  acceptance of Homoeopathy is  gaining momentum in view of its  harmlessness, easy affordability  and accessibility, safety,  efficacy, and gentle method of  administration of medicines. Due to  the increasing health challenges in  our country, the Govt. of India have  adopted the principle of “medical  pluralism”, giving more focus on  Complementary & Alternative  Medicines (CAM) including  Homoeopathy. The Ministry of  Ayush, Govt. of India have also  been encouraging the public to opt  health care service of their choice,  through the cafeteria mode.
Keywords: Health-One; Nation